Using the Biological Literature: A Practical Guide. - Lutishoor Salisbury (Issues in Science and Technology Librarianship, 2002)
This article reviews Using the Biological Literature: A Practical Guide. 3rd ed., rev., and expanded. New York: Dekker, 2002 by Diane Schmidt, Elizabeth B. Davis, and Pamela F. Jacobs.